Moving from Knowledge to Action: Blogging research and outcome highlights - Kristjanson, Patricia M.; Jost, Christine; Vervoort, Joost M.; Ferdous, N.; Schubert, Cecilia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This blog book tells the story of CCAFS research theme ‘Linking Knowledge with Action’; its approach and lessons learned throughout the years, especially 2014, while illustrating its many achievements through blogs and photos.